Mastering research writing: key takeaways from Write2Gether workshop series / Nik Ateerah Rasheeda Mohd Rocky, Aisyah Hasyila Jahidin and Gurmeet Kaur Surindar Singh - Mohd Rocky, Nik Ateerah Rasheeda; Jahidin, Aisyah Hasyila; Singh, Gurmeet Kaur Surindar (Faculty of Pharmacy, 2024)
The Write2Gether workshop is one of the many series organised by the Research Empowerment Unit, Faculty of Pharmacy Universiti Teknologi MARA (UiTM) aimed to promote the writing skills of the academic staff and postgraduate students, taking place on 5-7 August 2024. The event was designed to be resourceful for the participants who sought to develop their writing skills during the three-day event, which was held free of charge. On the first day of the workshop, Dr. Azwandi Ahmad, senior lecturer from the Department of Pharmacology and Life Sciences, Faculty of Pharmacy, UiTM Puncak Alam, explored the fundamental concepts of statistical analysis. He elaborated on the use of different statistical tests over lab-based as well as non-lab-based scenarios by pointing out their methodological and practical importance. He presented the participants with practical tips on which appropriate statistical tools to choose, a crucial skill that is required to ensure accuracy and validity in research data analysis.